Spherical molecular sieve drying agent and preparation method thereof

By using a mixed aqueous solution of NaOH and KOH for in-situ crystallization and potassium ion exchange during the molding process of the 3A spherical molecular sieve desiccant, the problems of decreased adsorption amount and insufficient strength caused by the use of binder are solved, and efficient water is achieved Adsorption and strength increase.

CN119425649APending Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310946443.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing 3A spherical molecular sieve desiccant uses binders during the molding process, resulting in a decrease in the amount of static and dynamic water adsorption, insufficient strength and burning base density, which increases the investment cost of the device and affects the adsorption rate.

Method used

By forming NaA molecular sieve raw powder, binder and additive in a ball forming equipment, and then contacting with a mixed aqueous solution of NaOH and KOH for in situ crystallization and potassium ion exchange, the production process is simplified and the production cost is reduced. Energy consumption.

Benefits of technology

The static and dynamic water adsorption amount, strength and scorching bulk density of the desiccant are improved, the selective adsorption capacity of water is enhanced, the amount of binder is reduced, and the process flow is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004366783650000081
    Figure BDA0004366783650000081
  • Figure BDA0004366783650000091
    Figure BDA0004366783650000091
Patent Text Reader

Abstract

The invention provides a spherical molecular sieve desiccant which comprises 95.0-98.5% by mass of an A-type molecular sieve and 1.5-5.0% by mass of a matrix, the A-type molecular sieve is composed of a non-crystal transformation A-type molecular sieve and a crystal transformation generated A-type molecular sieve, more than 50% of cations of the A-type molecular sieve are occupied by potassium ions, the particle diameter of the desiccant is 1.0-1.4 mm, the dynamic water adsorption capacity is greater than or equal to 22.0%, and the particle size of the desiccant is 0.2-0.5 mm. The drying agent is high in static and dynamic water adsorption capacity, good in strength and large in burning bulk density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a spherical molecular sieve desiccant, in particular to a 3A spherical molecular sieve desiccant and a preparation method thereof. Background Art

[0002] 3A molecular sieve is a KA type molecular sieve, and its typical composition is 0.75K 2 O·0.25Na 2 O.Al 2 O 3 ·2SiO 2 4.5H 2 O, the effective pore size is 0.30-0.33nm. 3A molecular sieve is generally made by exchanging potassium ions in K salt or KOH for Na in NaA type molecular sieve. + ions, since the radius of potassium ions is Than Na + Ionic radius So potassium ions replace Na + The ions occupy the position of the octahedral ring of the A-type molecular sieve, blocking the octahedral ring pore to a certain extent, making the window aperture Reduce to Na in NaA molecular sieve + K + When the exchange rate reaches 25%, the pore size is significantly reduced, which is manifested as a decrease in the adsorption of most adsorbates. Finally, the pore size is so small that only polar water molecules can enter. Therefore, the cations in 3A molecular sieves do not have to be completely K. +Ions, GB / T10504-2017 stipulates that the K exchange rate of 3A molecular sieve raw powder should not be less than 40%. 3A molecular sieve has a small pore size, a high water adsorption capacity, and still has a relatively high water adsorption capacity at a lower water partial pressure and a higher temperature. Therefore, it is particularly suitable for deep dehydration of small molecule logistics. 3A molecular sieve has been widely used in the drying and dehydration of cracking gas, ethylene, propylene, hydrogen, etc., and can reduce the water content of these logistics to less than 1ppm. 3A molecular sieve has a very low adsorption capacity for nitrogen and is often used as a hollow glass desiccant. Artificially synthesized 3A molecular sieves are usually in the form of micron-sized fine powders, and a certain amount of binder must be added for agglomeration or extrusion molding to meet industrial application requirements. The addition of binder can make 3A molecular sieve into various shapes and greatly improve the strength of the molded body. However, the presence of binder will reduce the static water adsorption of 3A molecular sieve adsorbent per unit mass. In order to ensure the processing capacity of the adsorption tower, it is necessary to increase the size and specifications of the adsorption container and supporting components or equipment, and use more adsorbents, thereby increasing the investment cost of the device. In addition, the binder in the 3A molecular sieve adsorbent may also block the molecular sieve pores, affect the adsorption rate of the adsorbent to water molecules, and reduce the dynamic water adsorption capacity. GB / T10504-2017 stipulates that the static water adsorption of 3A molecular sieve raw powder [75% RH, (35±1)℃] should not be less than 24.5% by weight, and the static water adsorption of 3A spherical molecular sieve superior products [75% RH, (35±1)℃] should not be less than 21.0% by weight. The latter index is only about 85.7% of the former, which is mainly due to the use of a certain amount of binder in the molding process of 3A spherical molecular sieve. In addition to the static water adsorption capacity, GB / T10504-2017 also stipulates various properties of 3A spherical molecular sieves, such as bulk density, particle size, crushing resistance, dynamic water adsorption capacity, static ethylene adsorption capacity, etc. Among them, the dynamic water adsorption capacity is better than the static water adsorption capacity to represent the actual water absorption capacity of the adsorbent.

[0003] CN101053978A mixes molecular sieve raw powder and clay in a certain proportion, binds them with a liquid silicate binder to form particles, and then dries or roasts them at 200-700°C to obtain a finished desiccant.

[0004] CN103721673A adopts two exchanges to reduce the consumption of potassium salt during K exchange, wherein the second exchange uses fresh KCl solution and the first exchange uses the exchange mother solution of the second exchange.

[0005] In order to reduce the powdering degree of the molecular sieve adsorbent, CN111362276A adopts common clay and molecular sieve to form a mold, and then coats the molded body with a layer of high-viscosity clay.

[0006] CN113697824A discloses a method for preparing a modified 3A molecular sieve, comprising: (1) granulating kaolin and 4A zeolite to obtain molecular sieve particles; (2) coating the molecular sieve particles with clay, activating and calcining the particles to obtain a calcined molecular sieve; the clay used for the clay coating is kaolin; (3) alkalizing the calcined molecular sieve obtained in step (2) to convert it into a binder-free molecular sieve; (4) exchanging the binder-free molecular sieve with potassium, controlling the potassium exchange degree to 30-60%, and drying the particles to obtain a potassium-exchanged molecular sieve; and (5) calcining the potassium-exchanged molecular sieve once, blowing off dust, and calcining the molecular sieve twice, wherein the primary calcination and the secondary calcination are carried out under a controlled atmosphere, wherein the controlled atmosphere is air with a dew point of -20-10°C. Summary of the invention

[0007] The object of the present invention is to provide a spherical molecular sieve desiccant and a preparation method thereof, wherein the desiccant has high static and dynamic water adsorption capacity, good strength and high basic bulk density.

[0008] The spherical molecular sieve desiccant provided by the present invention comprises 95.0-98.5% by mass of type A molecular sieve and 1.5-5.0% by mass of a matrix, wherein the type A molecular sieve is composed of a non-crystallized type A molecular sieve and a type A molecular sieve generated by crystallization, more than 50% of the cation sites of the type A molecular sieve are occupied by potassium ions, the particle diameter of the desiccant is 1.0-1.4 mm, and the dynamic water adsorption capacity is ≥22.0%.

[0009] The present invention provides a method for preparing the above-mentioned desiccant, comprising the following steps:

[0010] (1) adding NaA molecular sieve raw powder, a binder, and an additive into a rolling ball forming device to form a spherical desiccant first intermediate;

[0011] (2) subjecting the spherical desiccant first intermediate obtained in step (1) to a first drying and a first calcination treatment to obtain a desiccant second intermediate;

[0012] (3) contacting the desiccant second intermediate obtained in step (2) with a crystallization exchange liquid, simultaneously performing in-situ crystallization and potassium ion exchange, and then washing, a second drying, and activation roasting, wherein the crystallization exchange liquid is an aqueous solution containing NaOH and KOH.

[0013] The method forms the NaA molecular sieve raw powder and the binder, and then contacts them with a mixed aqueous solution of NaOH and KOH, so as to complete the two steps of in-situ crystallization of the binder into A-type molecular sieve and ion exchange of the NaA molecular sieve into KA molecular sieve in one step. Compared with the traditional process of first crystallization and then potassium ion exchange, the desiccant K +The ion exchange degree is appropriate, the performance is equivalent, the potassium dosage is reduced, the production process is simplified, and the investment in production equipment and the material consumption and energy consumption of the equipment are significantly reduced. The binder dosage of the present invention is relatively high, which can reduce the cost of raw materials, and the binder can be in-situ crystallized into a type A molecular sieve, so that the static and dynamic water adsorption capacity, strength, and basic bulk density of the desiccant are improved; after ion exchange, the cation position of the type A molecular sieve is partially occupied by potassium ions, and the 4A molecular sieve is converted into a 3A molecular sieve, which further improves the selective adsorption of water by the desiccant. DETAILED DESCRIPTION

[0014] In a first aspect, the present invention provides a spherical molecular sieve desiccant, comprising 95.0-98.5% by mass of a type A molecular sieve and 1.5-5.0% by mass of a matrix, preferably comprising 97.0-98.5% by mass of a type A molecular sieve and 1.5-3.0% by mass of a matrix, wherein the type A molecular sieve is composed of a non-crystallized type A molecular sieve and a crystallized type A molecular sieve, and more than 50% of the cationic sites of the type A molecular sieve are occupied by potassium ions.

[0015] The desiccant provided by the present invention has a diameter of 1.0 to 1.4 mm, preferably 1.0 to 1.2 mm, a dynamic water adsorption capacity of ≥22.0%, preferably ≥22.2%, a static water adsorption capacity of ≥24.0%, preferably ≥24.2%, a calcined bulk density of ≥0.77 g / mL, preferably ≥0.78 g / mL, and a crushing resistance of ≥43 N, preferably ≥45.

[0016] The non-crystallized A-type molecular sieve is obtained by potassium ion exchange of NaA molecular sieve, and the average crystal grain size of the NaA molecular sieve is 2-4 μm. The matrix is ​​the remaining material after the binder is subjected to in-situ crystallization treatment, and the binder is halloysite. The non-crystallized A-type molecular sieve accounts for 20%-45% of the total mass of the A-type molecular sieve in the desiccant, preferably 23%-39%.

[0017] In a second aspect, the present invention provides a method for preparing the adsorbent, comprising the following steps:

[0018] (1) adding NaA molecular sieve raw powder, a binder, and an additive into a rolling ball forming device to form a spherical desiccant first intermediate;

[0019] (2) subjecting the spherical desiccant first intermediate obtained in step (1) to a first drying and a first calcination treatment to obtain a desiccant second intermediate;

[0020] (3) contacting the desiccant second intermediate obtained in step (2) with a crystallization exchange liquid, simultaneously performing in-situ crystallization and potassium ion exchange, and then washing, a second drying, and activation roasting, wherein the crystallization exchange liquid is an aqueous solution containing NaOH and KOH.

[0021] According to the method of the present invention, the average crystal size of the NaA molecular sieve raw powder in step (1) is 2 to 4 μm, and the NaA molecular sieve of this crystal size is conducive to improving the bulk density of the desiccant; the binder is halloysite, which is the only natural kaolinite hydrate on the earth. Generally, the viscosity of halloysite is higher than that of clay minerals such as kaolin and attapulgite. Halloysite has the same silicon-aluminum ratio as type A molecular sieve, which provides natural convenience for its transformation into type A molecular sieve. According to the degree of hydration, it can be mainly divided into 10 angstrom-halloysite and 7 angstrom-halloysite. The chemical formula of 10 angstrom-halloysite is Al 2 O 3 ·2SiO 2 ·4H 2 O, its basic structure is a layer of water molecules sandwiched between kaolinite sheets, 7-angstrom-halloysite is the dehydration product of 10-angstrom-halloysite, sometimes also called meta-halloysite, and the viscosity of 10-angstrom-halloysite is significantly higher than that of 7-angstrom-halloysite. In the halloysite used in the present invention, 10-angstrom-halloysite accounts for more than 70% by weight, preferably 75-90% by weight; the auxiliary agent is one or more of sesbania powder, corn starch, carboxymethyl cellulose and bayberry tannin extract, preferably one of sesbania powder, corn starch, carboxymethyl cellulose and bayberry tannin extract in combination.

[0022] According to the method of the present invention, the content of the binder in step (1) is 25-45% of the total mass of the NaA molecular sieve raw powder and the binder, the content of the auxiliary agent is 2-4% of the total mass of the NaA molecular sieve raw powder and the binder, and the average grain size of the NaA molecular sieve raw powder is 2-4 μm.

[0023] According to the method of the present invention, the ball forming equipment in step (1) can be a high-speed granulator or a sugar coating machine or a disc granulator or other ball forming equipment.

[0024] According to the method of the present invention, in step (2), the halloysite in the first intermediate of the spherical desiccant is converted into reactive aluminosilicate by drying and high-temperature calcination, wherein the first drying temperature is 80 to 150° C. and the time is 1 to 4 hours; the first calcination temperature is 500 to 760° C. and the time is 2 to 4 hours.

[0025] According to the method of the present invention, in step (3), the second intermediate of the desiccant is contacted with a crystallization exchange liquid to crystallize the reactive aluminosilicate into a type A molecular sieve, and more than 50% of the sodium ions in the NaA type molecular sieve are exchanged for potassium ions. The crystallization exchange liquid is an aqueous solution containing NaOH and KOH, in which the concentration of NaOH is 0.7 to 1.5 mol / L, the concentration of KOH is 1.2 times or more of NaOH, preferably 1.2 to 5 times, and the ratio of the crystallization exchange liquid to the second intermediate of the desiccant is 2 to 10 L / kg, preferably 2.5 to 10 L / kg. The in-situ crystallization and potassium ion exchange temperature is 90 to 98°C, the water washing temperature is 90 to 98°C, and the water washing end point is the pH of the washing water 9 to 11; the second drying temperature is 80 to 150°C, and the time is 1 to 4 hours; the activation roasting temperature is 250 to 500°C, and the time is 1 to 2 hours.

[0026] According to the method of the present invention, since the moisture content of the second intermediate of the desiccant is very low, the water absorption and heat release are obvious, which may easily cause the thin strips to burst. Therefore, it needs to be pre-wetted before being loaded into the column container so that the moisture content of the second intermediate is increased to more than 20% by weight.

[0027] According to the method of the present invention, in step (3), the in-situ crystallization and potassium ion exchange can be carried out in a kettle container or a column container, preferably in a column container, and a plurality of the column containers can be connected in series or in parallel, the column container is filled with the second intermediate of the desiccant, and the crystal exchange liquid passes through the column container from bottom to top, and the volume space velocity is 0.5 to 2.0 h -1 , water without sodium or potassium ions, aqueous solution containing only NaOH, and aqueous solution containing NaOH and KOH flow out from the top of the column container in sequence, wherein the water without sodium or potassium ions can be collected as recycled water, and the aqueous solution containing only NaOH can be used to prepare the crystal exchange solution without the need for additional NaOH, and the excess effluent containing only NaOH can be discharged from the system, or recycled for standby use or evaporated to prepare crude alkali. The water washing can be carried out in a kettle container or a column container, preferably in a column container. After the in-situ crystallization and potassium ion exchange are completed, the washing water passes through the column container from bottom to top, and the volume space velocity is 2 to 5 h -1 The effluent from the top of the column container, i.e., the washing water, contains NaOH and KOH, which can be used to prepare the crystal exchange solution. KOH will not flow out of the system, and the utilization rate of K is high. It can be used entirely for ion exchange to convert the 4A molecular sieve into the 3A molecular sieve. When washing after the crystal exchange is completed, the surface of the desiccant is flushed while washing away the residual crystal exchange solution, thereby improving the surface finish and significantly reducing the degree of powder falling of the desiccant. In addition, the washing water flowing out from the top of the column container can continue to be used for the preparation of the crystal exchange solution, saving water consumption during the preparation process.

[0028] The present invention is further described below in conjunction with embodiments and comparative examples, but the actual protection scope of the present invention is not limited thereto.

[0029] The NaA molecular sieves used in the examples and comparative examples were purchased from Sinopec Catalyst Qilu Branch, with a static water adsorption capacity of 24.8%, and the origin of the halloysite was Hunan. The masses of the NaA molecular sieve raw powder and halloysite in the examples were all ignition-based masses, and the ignition reduction test conditions were calcined at 600°C for 2h.

[0030] The static water adsorption of the samples in the examples and comparative examples was determined according to the GB / T 6287-2021 method, and the dynamic water adsorption was determined according to the GB / T 8770-2014 method.

[0031] The crushing resistance of the desiccant in the examples and comparative examples was measured according to the method specified in HG / T 2783.

[0032] The method for determining the ignition density of the desiccant in the examples and comparative examples is as follows: take an appropriate amount of desiccant that has absorbed water in the air to a constant weight, put it into a glass measuring cylinder, place it on a tap density meter and vibrate it for 5 minutes, and then read the volume V (mL), wherein the amplitude is 3 mm and the vibration frequency is 290 times / min. Then weigh the net weight M of the sample, and then take an appropriate amount of the sample to test its ignition loss L (%) at 600°C, then the ignition density (g / mL) of the adsorbent is M*(1-L) / V.

[0033] The calculation method of K exchange degree of the desiccant samples in the embodiments and comparative examples is as follows: X-ray fluorescence spectrometry (XRF) is used to analyze the Na 2 O and K 2 The mass percentage of O is denoted as M N and M k , K exchange degree = M K / M K2O / (M k / M k2O +M N / M Na2O ), M k2O and M Na2O K 2 O and Na 2 The molar mass of O.

[0034] Example 1

[0035] 75kg of NaA molecular sieve powder with an average grain size of 2.5μm, 25kg of halloysite, 2kg of sesbania powder, and 2kg of bayberry tannin extract were mixed evenly, wherein the content of 10 angstroms-halloysite in the halloysite was 70% by mass, and an appropriate amount of deionized water was added, and the balls were rolled into balls, and small balls with a diameter of 1.0-1.4mm were screened to obtain the first intermediate of the desiccant, and then dried at 80°C for 4h, and calcined at 760°C for 4h to obtain the second intermediate of the desiccant. 245mL of the second intermediate of the desiccant was pre-wetted to constant weight at 35°C and a relative humidity of 75%, so that the small balls fully absorbed water and released heat, and then contacted with 1000mL of a crystal exchange liquid with a NaOH concentration of 0.77mol / L and a KOH concentration of 2.53mol / L in a reactor at 95°C for 4h to carry out in-situ crystallization and K + Ion exchange was performed and filtration was performed to obtain 900 mL of filtrate and solid. The solid was washed with water at 95°C until the pH of the washing water reached 10, then dried at 90°C for 2 h, and activated and calcined at 250°C for 2 h to obtain a desiccant product, numbered 3A-1.

[0036] The filtrate contains 1.54 mol / L NaOH and 1.75 mol / L KOH. Take 500 mL of the filtrate and add 500 mL of a 3.31 mol / L KOH solution to prepare 1000 mL of a 0.77 mol / L NaOH and 2.53 mol / L KOH solution. Therefore, 500 mL of 3.31 mol / L KOH solution is actually required for every 245 mL of the second intermediate of the desiccant.

[0037] Example 2

[0038] 70 kg of NaA molecular sieve raw powder with an average grain size of 2 μm, 30 kg of halloysite, 2 kg of sesbania powder, and 2 kg of bayberry tannin extract are mixed evenly, wherein the content of 10 angstrom-halloysite in the halloysite is 75% by mass, and an appropriate amount of deionized water is added, and the mixture is rolled into a ball to obtain a spherical desiccant first intermediate with a diameter of 1.0 to 1.4 mm, and then dried at 85° C. for 2 h and calcined at 720° C. for 3.5 h to obtain a desiccant second intermediate. Take the second intermediate of the desiccant and pre-wet it to constant weight at 35°C and relative humidity of 75%. After the thin strips fully absorb water and release heat, load them into a crystal exchange column with a filling volume of 245 mL. Pump the crystal exchange liquid into the bottom of the crystal exchange column and let it flow out from the top of the column until potassium ions are detected in the effluent from the top of the column. Pump the washing water into the bottom of the crystal exchange column and let it flow out from the top of the column until the pH of the top effluent is 10. Collect the effluent from the top of the column in sections, wherein the concentrations of NaOH and KOH in the crystal exchange liquid are 0.70 mol / L and 0.84 mol / L, respectively, and the volumetric space velocity of the crystal exchange liquid is 1.0 h -1 , the wash water volume space velocity is 2.0h -1The crystal exchange and water washing temperatures were both 95°C. After water washing, the unloading agent was dried at 80°C for 2h and activated and calcined at 500°C for 2h to obtain a desiccant product, numbered 3A-2. The analysis and evaluation results are shown in Table 1.

[0039] The above-mentioned crystal exchange uses 1000mL of crystal exchange liquid, and 710mL of 1.2mol / L NaOH solution is collected at the top of the crystal exchange column, which is called solution B2, and 195mL of 0.60mol / L NaOH and 0.65mol / L KOH mixed solution is called solution C2. Take 486mL of solution B2, 195mL of solution C2, and then add 319mL of 2.23mol / L KOH solution to mix into 1000mL of original crystal exchange liquid. Therefore, 319mL of 2.23mol / L KOH solution is actually required for every 245mL of desiccant second intermediate crystal exchange, and 224mL of 1.2mol / L NaOH solution is produced as a by-product.

[0040] Example 3

[0041] 60 kg of NaA molecular sieve raw powder with an average grain size of 4 μm, 40 kg of halloysite, 2 kg of starch, and 2 kg of bayberry tannin extract were evenly mixed, wherein the content of 10 angstrom-halloysite in the halloysite was 80% by mass. An appropriate amount of deionized water was added and the mixture was rolled into a ball to obtain a spherical desiccant first intermediate with a diameter of 1.0 to 1.4 mm. The mixture was then dried at 120° C. for 3 h and calcined at 540° C. for 2 h to obtain a desiccant second intermediate. Take the second intermediate of the desiccant and pre-wet it to constant weight at 35°C and relative humidity of 75%, allow it to fully absorb water and release heat, then load it into a crystal exchange column with a filling volume of 245 mL, pump the crystal exchange liquid into the bottom of the crystal exchange column, and let it flow out from the top of the column until potassium ions are detected in the effluent from the top of the column, then pump the washing water into the bottom of the crystal exchange column, let it flow out from the top of the column until the pH of the top effluent is 10, collect the effluent from the top of the column in sections, wherein the concentrations of NaOH and KOH in the crystal exchange liquid are 1.5 mol / L and 1.8 mol / L, respectively, and the space velocity of the crystal exchange liquid is 0.8 h -1 , water wash water air velocity is 4h -1 The crystal exchange and water washing temperatures were both 90°C. The unloading agent was dried at 100°C for 4 hours and activated and calcined at 450°C for 2 hours to obtain a desiccant product, numbered 3A-3. The analysis and evaluation results are shown in Table 1.

[0042] The above-mentioned crystal exchange uses 600 mL of crystal exchange liquid, and 280 mL of 2.59 mol / L NaOH solution is collected at the top of the crystal exchange column, which is called solution B3, and 193 mL of 1.31 mol / L NaOH and 1.52 mol / L KOH mixed solution is called solution C3. Take 250 mL of solution B3 and 193 mL of solution C3, and then prepare 157 mL of 5.01 mol / L KOH solution to mix into 600 mL of original crystal exchange liquid. Therefore, 157 mL of mol / L KOH solution is actually required for every 245 mL of desiccant second intermediate crystal exchange, and 30 mL of 2.59 mol / L NaOH solution is produced as a by-product.

[0043] Example 4

[0044] 75 kg of NaA molecular sieve raw powder with an average grain size of 3 μm, 25 kg of halloysite, and 2 kg of carboxymethyl cellulose are mixed evenly, wherein the content of 10 angstroms-halloysite in the halloysite is 80% by mass, an appropriate amount of deionized water is added, and ball forming is performed to obtain a spherical desiccant first intermediate with a diameter of 1.0 to 1.4 mm, and then dried at 150° C. for 1 hour and calcined at 650° C. for 4 hours to obtain a desiccant second intermediate. Take the second intermediate of the desiccant and pre-wet it at 35°C and 75% relative humidity until the ball has constant weight, so that it can fully absorb water and release heat, and then load it into a crystal exchange column with a filling volume of 245 mL. Pump the crystal exchange liquid into the bottom of the crystal exchange column and let it flow out from the top of the column until potassium ions are detected in the effluent from the top of the column. Then pump the washing water into the bottom of the crystal exchange column and let it flow out from the top of the column until the pH of the top effluent is 10. Collect the effluent from the top of the column in sections, wherein the concentrations of NaOH and KOH in the crystal exchange liquid are 1.0 mol / L and 1.5 mol / L, respectively, and the volumetric space velocity of the crystal exchange liquid is 1.8 h -1 , the wash water volume space velocity is 3.5h -1 The crystal exchange and water washing temperatures were both 98°C. The unloading agent was dried at 120°C for 4h and activated and calcined at 250°C for 2h to obtain a desiccant product, numbered 3A-4. The analysis and evaluation results are shown in Table 1.

[0045] The above-mentioned crystal exchange uses 700mL of crystal exchange liquid, and 395mL of 1.98mol / L NaOH solution is collected at the top of the crystal exchange column, which is called solution B4, and 198mL of 0.89mol / L NaOH and 1.26mol / L KOH mixed solution is called solution C4. Take 265mL of solution B4 and 198mL of solution C4, and then prepare 237mL of 3.37mol / L KOH solution, which can be mixed into 700mL of the original crystal exchange liquid. Therefore, 237mL of 3.37mol / L KOH solution is actually required for every 245mL of desiccant second intermediate crystal exchange, and 130mLmol / L NaOH solution is produced as a by-product.

[0046] Example 5

[0047] The desiccant was prepared according to the method of Example 1, using 1000 mL of crystal exchange liquid, except that the crystal exchange was carried out in a column container, and the concentrations of NaOH and KOH in the crystal exchange liquid were 0.70 mol / L and 0.84 mol / L, respectively. The filling volume of the second intermediate of the desiccant was 245 mL, and the crystal exchange liquid space velocity was 2 h -1 , water wash water air velocity is 4h -1 , a desiccant product was obtained, numbered 3A-5, and the analysis and evaluation results are shown in Table 1.

[0048] The above-mentioned crystal exchange uses 1000mL of crystal exchange liquid, and 585mL of 1.25mol / LNaOH solution is collected at the top of the crystal exchange column, which is called solution B5, and 202mL of 0.58mol / L NaOH and 0.64mol / L KOH mixed solution is called solution C5. Take 466mL of solution B5 and 202mL of solution C5, and then prepare 332mL of 2.14mol / L KOH solution, which can be mixed into 1000mL of the original crystal exchange liquid. Therefore, 332mL of 2.14mol / L KOH solution is actually required for every 245mL of desiccant second intermediate crystal exchange, and 119mLmol / L NaOH solution is produced as a by-product.

[0049] Example 6

[0050] The desiccant was prepared according to the method of Example 5, except that the spherical desiccant first intermediate with a diameter of 1.0-1.2 mm was sieved to obtain a desiccant product numbered 3A-6. The analysis and evaluation results are shown in Table 1.

[0051] Comparative Example 1

[0052] Desiccant was prepared according to the method of Example 2, except that NaA molecular sieve raw powder with an average crystal particle size of 0.5 μm was used. Four columns of desiccant were obtained, which were recorded as 3A-D1. The analysis results are shown in Table 1.

[0053] Comparative Example 2

[0054] Desiccant was prepared according to the method of Example 2, except that kaolin was used instead of halloysite. Four columns of desiccant were obtained, which were marked as 3A-D2. The analysis results are shown in Table 1.

[0055] Comparative Example 3

[0056] The desiccant was prepared according to the method of Example 2, except that the crystal exchange solution did not contain NaOH and the KOH concentration was 0.84 mol / L. The obtained desiccant was numbered 3A-D3. The analysis results are shown in Table 1.

[0057] Comparative Example 4

[0058] Desiccants were prepared according to the method of Example 2, except that the content of 10 angstrom-halloysite in the halloysite was 50% by mass. The obtained desiccants were numbered 3A-D4, and the analysis results are shown in Table 1.

[0059] Comparative Example 5

[0060] Desiccant was prepared according to the method of Example 2, except that the amount of NaA molecular sieve raw powder used was 90 kg, and the amount of halloysite used was 10 kg. The obtained desiccant was numbered 3A-D5, and the analysis results are shown in Table 1.

[0061] Comparative Example 6

[0062] The desiccant was prepared according to the method of Example 2, except that a spherical desiccant first intermediate with a diameter of 1.5 to 1.7 mm was sieved. The obtained desiccant numbers were 3A-D6, and the analysis results are shown in Table 1.

[0063] Table 1 Sample analysis and evaluation results in Examples and Comparative Examples

[0064]

[0065]

[0066] As shown in Table 1, compared with the desiccant 3A-2 prepared in Example 2, when preparing desiccant 3A-D1 in Comparative Example 1, the average grain size of the NaA molecular sieve raw powder used is smaller, and the calcined bulk density of desiccant 3A-D1 is smaller than that of 3A-2; when preparing desiccant 3A-D2 in Comparative Example 2, kaolin is used instead of halloysite, and its crushing resistance is smaller than that of 3A-2, indicating that its strength is poor; when preparing desiccant 3A-D3 in Comparative Example 3, the crystal exchange liquid does not contain NaOH, and the content of type A molecular sieve in desiccant 3A-D3 is lower than that of 3A-2, indicating that its crystal exchange effect is poor, and the dynamic water adsorption capacity of desiccant 3A-D3 is significantly lower than that of 3A-2; when preparing desiccant 3A-D4 in Comparative Example 4, 10 angstroms-haloysite with a halloysite content of 50% by mass is used, and the desiccant 3A-D4 is prepared. The content of type A molecular sieve in desiccant 3A-D4 is lower than that in 3A-2, indicating that its crystallization effect is poor. The static water adsorption and dynamic water adsorption of desiccant 3A-D4 are lower than those of 3A-2, and its crushing resistance is also lower, indicating that its strength is poor. When preparing desiccant 3A-D5 in comparative example 5, the binder content is 10% of the total mass of NaA molecular sieve original powder and binder, and the proportion of non-crystallized type A molecular sieve in the desiccant 3A-D5 to all molecular sieves is lower than that in 3A-2, and its crushing resistance is also lower, indicating that its strength is poor. When preparing desiccant 3A-D6 in comparative example 6, a spherical desiccant first intermediate with a diameter of 1.5 to 1.7 mm is screened, that is, the particle size of desiccant 3A-D6 is 1.5 to 1.7 mm, which is larger than that of 3A-2, and its dynamic water adsorption is significantly reduced compared with 3A-2.

Claims

1. A method for preparing a spherical molecular sieve desiccant, comprising the following steps: (1) adding NaA molecular sieve raw powder, a binder, and an additive into a rolling ball forming device to form a spherical desiccant first intermediate; (2) subjecting the spherical desiccant first intermediate obtained in step (1) to a first drying and a first calcination treatment to obtain a desiccant second intermediate; (3) contacting the second intermediate of the desiccant obtained in step (2) with a crystallization exchange liquid, and simultaneously performing in-situ crystallization of the binder and potassium ion exchange, and then washing, a second drying, and activation roasting, wherein the crystallization exchange liquid is an aqueous solution containing NaOH and KOH.

2. The method according to claim 1, characterized in that In step (1), the binder is halloysite, and the auxiliary agent is one or more of sesbania powder, corn starch, carboxymethyl cellulose and bayberry tannin extract.

3. The method according to claim 2, characterized in that In step (1), the content of 10 angstrom-halloysite in the halloysite is 70 wt % or more, preferably 75 to 90 wt %.

4. The method according to claim 1, characterized in that In step (1), the binder content is 25-40% of the total mass of the NaA molecular sieve raw powder and the binder, the auxiliary agent content is 2-4% of the total mass of the NaA molecular sieve raw powder and the binder, and the average grain size of the NaA molecular sieve raw powder is 2-4 μm.

5. The method according to claim 1, characterized in that In step (2), the first drying temperature is 80-150° C., and the time is 1-4 hours; the first calcination temperature is 500-760° C., and the time is 2-4 hours.

6. The method according to claim 1, characterized in that In step (3), in the crystal exchange liquid, the concentration of NaOH is 0.5-1.5 mol / L, the concentration of KOH is 1.2 times or more of that of NaOH, and the ratio of the crystal exchange liquid to the second intermediate of the desiccant is 2-10 L / kg.

7. The method according to claim 1, characterized in that In step (3), the in-situ crystallization and potassium ion exchange temperature is 90-98°C.

8. The method according to claim 1, characterized in that The K ion exchange degree of the desiccant is ≥50%.

9. The method according to claim 1, characterized in that In step (3), the in-situ crystallization and potassium ion exchange are carried out in a column container, the column container is filled with the second intermediate of the desiccant, and the crystal exchange liquid passes through the column container from bottom to top, and the volume space velocity is 0.5 to 2.0 h -1 .

10. The method according to claim 9, characterized in that The washing is carried out in a column container, and the washing water passes through the column container from bottom to top, with a volume space velocity of 2 to 5 h -1 .

11. The method according to claim 9, characterized in that A plurality of the column containers are connected in series or in parallel.

12. The method according to claim 1, characterized in that In step (3), the water washing temperature is 90-98°C, and the water washing end point is the pH of the washing water is 9-11; the second drying temperature is 80-150°C, and the time is 1-4 hours; the activation roasting temperature is 250-500°C, and the time is 1-2 hours.

13. A spherical molecular sieve desiccant prepared by any one of the methods of claims 1 to 12.

14. A spherical molecular sieve desiccant, comprising 95.0-98.5% by mass of a type A molecular sieve and 1.5-5.0% by mass of a matrix, wherein the type A molecular sieve is composed of a non-crystallized type A molecular sieve and a type A molecular sieve generated by crystallization, more than 50% of the cationic sites of the type A molecular sieve are occupied by potassium ions, the desiccant has a diameter of 1.0-1.4 mm, and a dynamic water adsorption capacity of ≥22.0%.

15. The desiccant according to claim 14, characterized in that The non-crystallized A-type molecular sieve is obtained by exchanging NaA molecular sieve with potassium ions, and the average crystal grain size of the NaA molecular sieve is 2 to 4 μm.

16. The desiccant according to claim 14, characterized in that The matrix is ​​the remaining material after the binder is subjected to in-situ crystallization treatment, and the binder is halloysite.

17. The desiccant according to claim 14, characterized in that The diameter of the desiccant is 1.0 to 1.2 mm.

18. The desiccant according to claim 14, characterized in that The non-crystallized A molecular sieve accounts for 20% to 45% of the total mass of the A molecular sieve in the desiccant.

19. The desiccant according to claim 14, characterized in that The static water adsorption capacity of the desiccant is ≥24.0%, the bulk density is ≥0.77 g / mL, and the average crushing resistance is ≥43N.

Citation Information

Patent Citations

  • Method for preparing molecular sieves dryer special used for pneumatic braking system

    CN101053978A

  • High-adsorption low-powder-falling zero-pollution 3A molecular sieve and forming process and application thereof

    CN111362276A

  • Preparation process and application of modified 3A molecular sieve

    CN113697824A

  • Preparation method of K-A molecular sieve

    CN103721673A

  • Preparation method of special molecular sieve for ethylene

    CN106082256A

Cited By

  • Crystallization-ion exchange one-step preparation method of binder-free 3A molecular sieve

    CN120771830A